2010
DOI: 10.1186/1472-6963-10-40
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender and parenthood on physicians' careers - professional and personal situation seven years after graduation

Abstract: BackgroundThe profile of the medical profession is changing in regard to feminization, attitudes towards the profession, and the lifestyle aspirations of young physicians. The issues addressed in this study are the careers of female and male physicians seven years after graduation and the impact of parenthood on career development.MethodsData reported originates from the fifth assessment (T5) of the prospective SwissMedCareer Study, beginning in 2001 (T1). At T5 in 2009, 579 residents (81.4% of the initial sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
195
0
25

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(232 citation statements)
references
References 34 publications
12
195
0
25
Order By: Relevance
“…As mesmas pesquisas que apontam a crescente feminização da medicina indicam também a teimosa persistência da discriminação e do hiato de gênero na profissão. Pesquisas que se dedicam a estudar e comparar o processo de formação de homens e mulheres na medicina concluem que as mulheres médicas sofrem significativo impacto negativo provocado por estereótipos sexistas e discriminação de gênero já durante os anos de formação 12,14,15,21 . Formas sutis de discriminação encontram-se profundamente enraizadas na cultura médica e fazem com que homens e mulheres não estejam em situação de igualdade.…”
Section: A Persistência Da Discriminação De Gênerounclassified
See 2 more Smart Citations
“…As mesmas pesquisas que apontam a crescente feminização da medicina indicam também a teimosa persistência da discriminação e do hiato de gênero na profissão. Pesquisas que se dedicam a estudar e comparar o processo de formação de homens e mulheres na medicina concluem que as mulheres médicas sofrem significativo impacto negativo provocado por estereótipos sexistas e discriminação de gênero já durante os anos de formação 12,14,15,21 . Formas sutis de discriminação encontram-se profundamente enraizadas na cultura médica e fazem com que homens e mulheres não estejam em situação de igualdade.…”
Section: A Persistência Da Discriminação De Gênerounclassified
“…De uma profissão dominada pelos homens, a medicina passa a ser uma profissão em que a maioria dos novos licenciados são mulheres, e, ao menos nos países mais urbanizados e industrializados, essa tendência representa um fenômeno global 2,3,8,10,11 . Em países como Reino Unido, Austrália, Canadá, Estados Unidos 12,13 , Suíça, Alemanha 14,15 e Holanda 16 , as mulheres representam em torno de 60% dos novos licenciados. Na Austrália e em Portugal, no final da década de 1990, elas já representavam, respectivamente, 68% e 69% dos novos ingressantes 13,10 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Specialty choice is complex, influenced by gender, career motivation and life goals, 8 as well as attitudes about social responsibility. 1 In a review of the North American literature published through 1993, Bland, Meurer and Maldonado identified student-and curriculum-related determinants of primary care specialty choice as described in their paper published in 1995 (Appendix 1).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of mentorship and the challenges of being a woman in residency training make residency the ideal time to initiate a mentoring relationship. Despite its importance, a recent study by Buddeberg-Fischer et al showed that female physicians were less likely to have a mentor than men (40.5 vs. 58.9 %) [5]. A mentorship needs survey of the psychiatry residents I conducted at McMaster University also showed that just 30 % of the female residents had a mentor (n=9/27), while 56 % of males did (n=5/9).…”
mentioning
confidence: 98%